2020
DOI: 10.3390/en13246639
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization and Evaluation of the Vibroacoustic Field of Hydraulic Pumps: The Case of an External Gear Pump

Abstract: This paper presents the experimental characterization of the vibroacoustic fields and the evaluation of noise performances of hydraulic pumps. Research on hydraulic pump noise has traditionally focused on the fluid-borne noise sources, and very often the analyses of vibration and noise have been performed focusing on a few local points. This trend results in the lack of investigation on the overall behaviors of vibroacoustic fields of hydraulic pumps, and it has been one of the obstacles to understand the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…It has a significant implication that can aid in the development of vibration reduction strategies from the source level. According to previous research by authors [35], the vibration field responses that the external gear pump exhibits during operation are similar to the superposition of the vibration modes observed in this study. This observation suggests that the overall structural vibrations can be reduced by suppressing the modal responses, which are proportional to the modal forces.…”
Section: Discussion On Vibration Reduction Strategies During Pump Ope...supporting
confidence: 89%
See 1 more Smart Citation
“…It has a significant implication that can aid in the development of vibration reduction strategies from the source level. According to previous research by authors [35], the vibration field responses that the external gear pump exhibits during operation are similar to the superposition of the vibration modes observed in this study. This observation suggests that the overall structural vibrations can be reduced by suppressing the modal responses, which are proportional to the modal forces.…”
Section: Discussion On Vibration Reduction Strategies During Pump Ope...supporting
confidence: 89%
“…Of all these components, the modal behaviors of the pump body are of primary interest. However, those of the mounting plate are examined as well since prior research done by the authors has shown that the mounting has a great contribution to the radiated noise during the operation of the pump [34,35].…”
Section: Reference Unit and Systemmentioning
confidence: 99%
“…Woo proposed a method to interpret and characterize the measured vibration sound field. [ 13 ] A test platform monitors the sound pressure level (SPL) and sound power level of the hydraulic pump. Experimental results show that this method can reliably evaluate the hydraulic pump's noise characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulic transmission and control power generation systems are easily disturbed by signals such as vibration and noise. Unfavorable noise is accompanied by the pressure pulsations in the flapper-nozzle valve flow field [28]. The noise and vibration of hydraulic pumps usually exhibit high spatial variations [29].…”
Section: Introductionmentioning
confidence: 99%